دور المحكمة الدستورية في الفصل في المنازعات الانتخابية في الجزائر - حنانة, محمد نذير (My University, 2022)
وأخيرا يمكن القول أنّ هذه الدراسة تهدف إلى إعطاء الدور الفعال للمحكمة الدستورية ودورها في مراقبة الانتخابات والسهر على تسييرها، كما درسنا تطور المحكمة الدستورية وتعريفها وتمييزها عن باقي المحاكم الأخرى ومنه التعديل الذي جاء به دستور 2020 أعطى للمحكمة الدستورية صلاحيات لاحترام وضمان الدستور وحماية مؤسسات الدولة واستقرارها وقد منح دستور 2020 عدة اختصاصات للمحكمة الدستورية منها الرقابية، والتي تكون على سبيل الجواز أو الوجوب تقوم على إثرها بالنظر في مدى مطابقة أحكام الدستور للتشريعات وأخرى استشارية من قبل الإطارات السامية في الدولة وعلى رأسها رئيس الجمهورية، فقد خصّصت عدة مواد في الدستور لرئيس الجمهورية الحق في استشارة رئيس المحكمة الدستورية في عدة قرارات يمكن اتخاذها، كما كرّس المؤسس الدستوري للمحكمة الدستورية الفصل في طعون الانتخابات الوطنية دون المحلية كون الانتخاب يمثّل الإرادة الشعبية للأفراد وهو حق دستوري مجسداً للسلطة مما يتطلب حماية قانونية.Finally, it can be said that this study aims to give the effective role of the Constitutional Court and its role in monitoring the elections and ensuring their conduct. The Constitution of 2020 granted the Constitutional Court jurisdictions, including oversight, which is a matter of permissibility or obligation based on its consideration of the extent to which the provisions of the Constitution comply with the legislation, and other advisory functions by the high officials in the state, led by the President of the Republic. Several articles in the Constitution have been allocated to the President of the Republic, the right to Consultation with the President of the Constitutional Court in several decisions that can be taken, and the constitutional founder of the Constitutional Court has dedicated to adjudicating challenges to national elections rather than local ones, since the election represents the popular
ماستر اداري
Keywords: دور، المحكمة ،الدستورية ، الفصل ، المنازعات، الانتخابية ، الجزائر; Role, Court, Constitutional, Separation, Disputes, Electoral, Algeria